The impact of Ontario's child restraint legislation on the incidence, severity and patterns of injury in children under five years. - Senzilet, Linda Debra. (University of Ottawa (Canada), 1992)
In 1983, the Ontario government introduced legislation which mandated the restraint of all child passengers under 50 pounds in restraint systems appropriate to their weight. The efficacy of such restraint systems has been proven, and standards for their manufacture have been set by the government of Canada. The objectives of this study were to determine whether Ontario's child restraint legislation has resulted in significant and sustained reductions in the incidence and severity of injury, as well as changes in the anatomical patterns of fatal and non-fatal injury. Data sources included the Hospital Medical Records Institute (HMRI) and Transport Canada's Traffic Accident Information Data Bank (TRAID). The study used the interrupted time-series design and autoregressive integrated moving average (ARIMA) modelling to analyze a variety of rates and indicators calculated for children under 5, as well as for a control group of adults 20-44 years old. The study period encompassed five pre-law years and five post-law years, extending from 1979 to 1988. Results suggested that there were no significant changes in either the incidence, severity or anatomical patterns of injury in children covered by the legislation. Two possible explanations for the apparent lack of an intervention effect are that either the pre- to post-legislation increase in (proper) usage rates was not large enough, or that any positive effects of the law were too gradual to be detected. These conclusions are supported by evidence that there was a relatively high usage of child restraints prior to the legislation, and that rates of proper wearing of restraints did not exceed 50% in the years following implementation. Child restraint laws cannot achieve their objectives without a higher level of sustained compliance. Several means of achieving this objective are presently being implemented by the so-called "95 by 95" program, i.e., the National Occupant Restraint Program that is operating in all provinces, and whose stated goal is a 95% wearing rate of restraints in all age groups by the year 1995. (Abstract shortened by UMI.)
Keywords: Health Sciences, Public Health.